The Implementation of Inclusive Education in Elementary Schools: A Study of Challenges and Opportunities - Ali Yusron (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the implementation of inclusive education in elementary schools by highlighting the various challenges and opportunities that arise. The method used is a qualitative approach through library research, employing content analysis techniques to evaluate and interpret data from relevant literature sources. The findings reveal that the implementation of inclusive education still faces obstacles such as limited resources, insufficient teacher training, and suboptimal facilities and infrastructure. Additionally, social and cultural factors, such as stigma toward students with special needs, also pose significant barriers. Nonetheless, there are considerable opportunities to improve the quality of education through strengthened regulations, enhanced educator capacity, adequate provision of facilities, and the development of an inclusive culture within schools and the wider community. A comprehensive approach and collaboration among stakeholders are key factors in the successful, effective, and sustainable implementation of inclusive education.